EXTREME U-TH DISEQUILIBRIUM IN RIFT-RELATED BASALTS, RHYOLITES AND GRANOPHYRIC GRANITE AND THE TIMESCALE OF RHYOLITE GENERATION, INTRUSION AND CRYSTALLIZATION AT ALID VOLCANIC CENTER, ERITREA - Lowenstern J.B.; Charlier B.L.A.; Clynne M.A.; Wooden J.L. (My University, 2006)
Rhyolite pumices and co-erupted granophyric (granite) xenoliths yield evidence for rapid magma generation and crystallization prior to their eruption at 15·2 ± 2·9 ka at the Alid volcanic center in the Danikil Depression, Eritrea. Whole-rock U and Th isotopic analyses show 230Th excesses up to 50% in basalts <10?000 years old from the surrounding Oss lava fields. The 15 ka rhyolites also have 30–40% 230Th excesses. Similarity in U–Th disequilibrium, and in Sr, Nd, and Pb isotopic values, implies that the rhyolites are mostly differentiated from the local basaltic magma. Given the (230Th/232Th) ratio of the young basalts, and presumably the underlying mantle, the (230Th/232Th) ratio of the rhyolites upon eruption could be generated by in situ decay in about 50?000 years. Limited (?5%) assimilation of old crust would hasten the lowering of (230Th/232Th) and allow the process to take place in as little as 30?000 years. Final crystallization of the Alid granophyre occurred rapidly and at shallow depths at ?20–25 ka, as confirmed by analyses of mineral separates and ion microprobe data on individual zircons. Evidently, 30?000–50?000 years were required for extraction of basalt from its mantle source region, subsequent crystallization and melt extraction to form silicic magmas, and final crystallization of the shallow intrusion. The granophyre was then ejected during eruption of the comagmatic rhyolites.
Keywords: U-series; zircon; ion microprobe; volcano; geochronology